Implementation of metal-free ring-opening polymerization in the preparation of aliphatic polycarbonate materials - Mespouille, Laetitia; Coulembier, Olivier; Kawalec, Michal; Dove, Andrew P.; Dubois, Philippe (Progress in polymer science, 2014)
Environmental concerns along with the need to develop aliphatic polycarbonate materials free of any toxic compounds have driven scientists to implement macromolecular engineering processes by replacing potentially toxic and carcinogenic metal-based catalysts traditionally used for the ring-opening polymerization of cyclic carbonates by organic compounds. This issue is of particular importance as aliphatic polycarbonates are gaining increasing credibility for biomedical applications owing to their biocompatibility and bioresorbability. This review provides a complete account of the various metal-free catalysts that has been developed so far as well as comprehensive investigations on the related polymerization mechanisms.